Halal Certification Issues In Pharmaceutical Products-CCM Berhad - Johar, Azlydia (2009)
This research explores the application of Halal certification issues in the pharmaceuticals industry in Malaysia. The company that had been chosen for this study is Chemical Company of Malaysia Berhad (CCM Berhad). The CCM is the biggest pharmaceutical company and also at the fore front of Halal application initiatives involving pharmaceuticals products in Malaysia. The company was concentrates to gaining market competitiveness in the local market as well as the foreign markets. The purpose of the study are: (1) to create an exclusive Halal certified prescription drugs or medicines line against its competitors (2) The key research is intended to focus on Halal application on pharmaceuticals product. This research employs a case study methodology. The key research is intended to focus on Halal application on pharmaceuticals product. A pharmaceutical product is defined as a licensed medicine that is regulated by legislation to require a prescription before it can be obtained.